The effectiveness of the Push Brace™ orthosis and corticosteroid injection for managing first carpometacarpal joint osteoarthritis: A factorial randomised controlled trial protocol. (June 2015) - Peters, Susan E; Jha, Bhavana; Couzens, Gregory B; Walsh, Wilma; Lisle, David; Ross, Mark
Introduction: Various conservative treatments for first carpometacarpal joint osteoarthritis have been reported. We aim to investigate the short-term effectiveness of conservative management interventions used to improve pain and function for adults with first carpometacarpal joint arthritis in a randomised controlled trial. Methods: A pragmatic 2 × 2 factorial randomised controlled trial will be conducted. This randomised controlled trial will have one control group (hand therapy) and three intervention groups. Interventions will include Push Brace™ orthosis and hand therapy, ultrasound-guided intra-articular corticosteroid injection and hand therapy and a combination of all three interventions. A total of 276 participants will be recruited for the trial. The primary outcomes will be pain (reported using a Visual Analogue Scale) and function (using the Patient Rated Wrist/Hand Evaluation). Secondary outcomes will include osteoarthritis specific function, pinch strength, global change and quality of life. Adverse events and complications will be reported. Outcomes assessments will be completed prior to the intervention and at 3, 6, 12 and 24 months post-intervention. The trial will be conducted at a private hand surgery clinic in Queensland, Australia. Conclusions: Results from this trial will contribute to the evidence on conservative management of first carpometacarpal osteoarthritis.